Network charging schemes and self-supply: Instruments to prevent self-reinforcing dynamics - Christine Brandstätt (Jacobs University Bremen, Bremen Energy Research (BER), 2021)
Self-supply can destabilize the finance of a distribution network. This paper analyses under which circumstances the tariff structure of a distribution network is stable or unstable under pressure of self-supply and provides recommendation how to change the tariff structure to restore stability if it is unstable. This paper analyses the occurrence of self-reinforcing dynamics in relation to volumetric network tariffs and surcharges in networks with a high propensity for self-supply. We model the level of self-supply endogenously depending on profitability and explore network tariffs that avoid an unstable dynamic for investments into self-supply in the system. Analysed tariff modifications concern the energy and load split, the extent of netting, and a variation in cost pass-through to lower network levels. Adding to the recent literature, we explore the option to calibrate tariff parameters predetermined as well as endogenously linked to self-supply levels in the network. We find endogenously determined modifications of load- and energy split and variations in the cost pass-through from upper network levels between parallel grids most promising to prevent a self-reinforcing dynamic. The analysed modifications also open up the possibility to calibrate a new, sustainable level of self-supply and to incorporate uncertainties in the tariff design.
Keywords: L11; L94; Q41; 330; network tariffs; electricity distribution; prosumers